1978
DOI: 10.1128/jb.136.3.833-838.1978
|View full text |Cite
|
Sign up to set email alerts
|

Cell fractions and enzymatic activities of Ureaplasma urealyticum

Abstract: The localization of some enzymic activities in cell fractions of Ureaplasma urealyticum was studied. A quantitative evaluation of the effectiveness of several cell lysis procedures was obtained by using labeled membranes and sucrose density gradient centrifugation. Ultrasonic treatment was found to be the most effective procedure for lysing the cells, whereas digitonin and osmotic shock caused the lysis of only 70 and 50% of the cells, respectively. The localization of selected enzymes in Ureaplasma cells rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1980
1980
2001
2001

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 14 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…The high inoculum density and the low initial urea concentration ensured a near depletion of the urea, allowing for the half substrate saturation constant ( K m ) to be estimated by a linearized form of the Michaelis‐Menten function. The estimated K m of 670 μM is in the lower range of K m values for ureases in other bacteria (ranging from 0.1 to >100 mM [47–54]), but it is tremendously high compared to other substrate capturing enzymes in bacteria (normally in the 0.1–1‐μM range, [55]). It is also very high compared to ambient bulk concentrations of urea in soil, which are in the 1–10‐μM range (Pedersen H, Ph.D. Thesis 1995, Aarhus University, Denmark).…”
Section: Discussionmentioning
confidence: 99%
“…The high inoculum density and the low initial urea concentration ensured a near depletion of the urea, allowing for the half substrate saturation constant ( K m ) to be estimated by a linearized form of the Michaelis‐Menten function. The estimated K m of 670 μM is in the lower range of K m values for ureases in other bacteria (ranging from 0.1 to >100 mM [47–54]), but it is tremendously high compared to other substrate capturing enzymes in bacteria (normally in the 0.1–1‐μM range, [55]). It is also very high compared to ambient bulk concentrations of urea in soil, which are in the 1–10‐μM range (Pedersen H, Ph.D. Thesis 1995, Aarhus University, Denmark).…”
Section: Discussionmentioning
confidence: 99%
“…Jeffries (90,91) demonstrated that urease activity in 22 species of bacteria was associated with soluble extracts of the cells, which were ruptured by sonication or French pressure cell lysis. In cell fractionation studies of K. aerogenes (59), U. urea'lticiun (44,145,189,236), Providencia stiuar-tii (158), and Protelus lirilbilis (98), the majority of urease partitioned with the soluble cytoplasmic fraction. Analysis for control enzymes, known to reside in specific cell fractions, supported the conclusion that urease is cytoplasmic in these species.…”
Section: Cellular Localization Of Ureasementioning
confidence: 99%
“…The possibility that ATP may be generated in some mycoplasmas, such as the ureaplasmas, through the formation of an ion gradient coupled to urea hydrolysis has recently been suggested (3). This hypothesis stems from the localization of urease and ATPase in the cytoplasm and membrane, respectively, of ureaplasmas (3,6). At physiological pH, urea is uncharged and presumably permeates the cell membrane freely.…”
mentioning
confidence: 99%
“…The strain of Ureaplasma urealyticum studied was P 108. The organisms were grown, harvested as previously reported (6), washed twice with 0.1 M sodium phosphate (pH 6.0), and suspended in a small volume of the same buffer. Protein was determined by the method of Lowry et al (2).…”
mentioning
confidence: 99%